Greening death : reclaiming burial practices and restoring our tie to the earth - Kelly, Suzanne, 1969- (Rowman and Littlefield, 2015)
"We once disposed of our dead in earth-friendly ways--no chemicals, biodegradable containers, dust to dust. But over the last 150 years death care has become a toxic, polluting, and alienating industry in the United States. Today, people are slowly waking up to the possibility of more sustainable and less disaffecting death care, reclaiming old practices in new ways, in a new age. Greening Death traces the philosophical and historical backstory to this awakening, captures the passionate on-the-ground work of the Green Burial Movement, and explores the obstacles and other challenges getting in the way of more robust mobilization. As the movement lays claim to greener, simpler, and more cost-efficient practices, something even more promising is being offered up--a tangible way of restoring our relationship to nature."--Publisher's description